Juridical Overview of the Mechanism for the Forest Area Release and Investment Facilities for Infrastructure Development in Nusantara Capital City - Haira, Haibati; Faradz, Haedah; Sanyoto, Sanyoto (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The relocation of the central government and the state capital to Nusantara Capital City is accompanied by infrastructure development in East Kalimantan, known as the world’s lungs because of its vast forest reserves, which have been designed as a national strategic priority project. This study examined and answered problems related to the identification of the use of forest areas for infrastructure development in Nusantara Capital and its forest realizing mechanism and the investment facility provided by the Indonesian government to boost the investment climate in Nusantara Capital. The research method used is a normative juridical approach. The main findings are the release mechanism for the convertible production forest carried out by Nusantara Capital City Authority for infrastructure development in Nusantara Capital City and the investment facility for its infrastructure development, including but not limited to granting fiscal and non-fiscal incentives.Keywords: forest area release; convertible production forest; state capital; infrastructure development; investment.